Proceedings of 13th Baltic Sea Geotechnical Conference 2016
DOI: 10.3846/13bsgc.2016.017
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Wood Fly Ash in Stabilization of Unbound Pavement Layers and Soils

Abstract: Modification and stabilization of road structure unbound layers has extensively been studied both at laboratory and field for decades. The most commonly used binders for soil modification and stabilization are cement and quicklime (CaO), but alternative pozzolans and their mixtures are of economical, technical and environmental interest. This study presents soil stabilization with wood fly ash (WFA) at laboratory. Natural sand (Sa), Sa mixtures with 10% and 20% WFA were compacted at optimal water content accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Field monitoring showed significant increases in stiffness and decreases in permeability over time, which were attributed to the hydration of ash. The self-cementitious property of PPFA arising from its high calcium and aluminosilicate contents can result in substantial improvements in the strength and volume change properties of expansive subgrades and foundation soils [20][21][22]105]. Due to very low permeability, PPFA-based geopolymers can also be successfully employed as hydraulic barriers, including for cover for landfills [106,107].…”
Section: Binder Components For Geotechnical Engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field monitoring showed significant increases in stiffness and decreases in permeability over time, which were attributed to the hydration of ash. The self-cementitious property of PPFA arising from its high calcium and aluminosilicate contents can result in substantial improvements in the strength and volume change properties of expansive subgrades and foundation soils [20][21][22]105]. Due to very low permeability, PPFA-based geopolymers can also be successfully employed as hydraulic barriers, including for cover for landfills [106,107].…”
Section: Binder Components For Geotechnical Engineering Applicationsmentioning
confidence: 99%
“…In order to withstand extreme conditions, the bacteria may enter a dormant stage, thereby decreasing the microbial population and diversity and ultimately disturbing the ecological balance. PPFA and value-added materials also have multifunctional engineering applications, such as supplementary cementitious material (SCM) in concrete systems, aggregate in pavement construction, binder for soil stabilization, and adsorbent for the immobilization of toxic heavy metals [15][16][17][18][19][20][21][22][23]. Based on a statistical survey conducted on the management and utilization of boiler ashes generated at Canadian pulp and paper mills, it was reported that more than 50% of ash is landfilled, 20-25% is used as a soil amendment (direct application or compost), and less than 20% is used for other beneficial applications such as the construction of embankment fills, the stabilization of pavement layers, and the solidification of wastes.…”
mentioning
confidence: 99%
“…In base layers it would be possible to use fine fly ash and coarser bottom ash due to two mechanisms: improvement of bearing capacity through mechanical stabilization and improved grading, or due to bioash action as a hydraulic binder. Laboratory testing of wood ash and ash produced by combustion of waste from paper mills reveal satisfactory values, and the use of such ash is significant [39][40][41]. However, contradictory results were obtained by field tests related to stabilization of layers of the existing (often forest) roads [30,41,42].…”
Section: Stabilized Base Layersmentioning
confidence: 99%
“…However, contradictory results were obtained by field tests related to stabilization of layers of the existing (often forest) roads [30,41,42]. Stabilization effect of the addition of 10 % and 20 % of wood ash to mixtures with sand was examined by Škels et al [39]. Their results revealed a multiple increase in the CBR value in both stabilized mixtures, without significant swelling.…”
Section: Stabilized Base Layersmentioning
confidence: 99%
“…The chemical composition of BA, especially the content of CaO and pozzolan, indicates the possibility of partial or complete replacement of traditional binders, cement, and lime during the stabilization of the subgrade materials with a lower load bearing capacity [ 10 , 11 , 12 , 13 , 14 , 15 ], in the base layers of pavement structures [ 16 , 17 , 18 , 19 , 20 ] or in concretes [ 21 , 22 ]. With the absence of binding properties, BA can be used as a replacement for a mineral filler or aggregate in asphalt mixtures, a filler in concretes, and as a replacement for smaller aggregate in base layers of pavement structures, depending on the fraction of ash.…”
Section: Introductionmentioning
confidence: 99%